ChemInform Abstract: Ruthenium‐Catalyzed Direct N‐Formylation of Lactams with Paraformaldehyde. Issue 38 (3rd September 2015) - Lee, Hoseong; Kang, Byungjun; Lee, Sang‐Ick; Hong, Soon Hyeok
Abstract Lactams are directly converted into N‐formylimides catalyzed with Shvo′s catalyst generating hydrogen as the only by‐product.